Exendin‐4 decreases liver inflammation and atherosclerosis development simultaneously by reducing macrophage infiltration. (February 2014) - Wang, Y; Parlevliet, E T; Geerling, J J; van der, S J L; Zhang, H; Bieghs, V; Jawad, A H M; Shiri‐Sverdlov, R; Bot, I; de, S C A; Havekes, L M; Romijn, J A; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose The aetiology of inflammation in the liver and vessel wall, leading to non‐alcoholic steatohepatitis (NASH) and atherosclerosis, respectively, shares common mechanisms including macrophage infiltration. To treat both disorders simultaneously, it is highly important to tackle the inflammatory status. Exendin‐4, a glucagon‐like peptide‐1 (GLP‐1) receptor agonist, reduces hepatic steatosis and has been suggested to reduce atherosclerosis; however, its effects on liver inflammation are underexplored. Here, we tested the hypothesis that exendin‐4 reduces inflammation in both the liver and vessel wall, and investigated the common underlying mechanism. Experimental Approach Female APOE*3‐Leiden.CETP mice, a model with human‐like lipoprotein metabolism, were fed a cholesterol‐containing Western‐type diet for 5 weeks to induce atherosclerosis and subsequently treated for 4 weeks with exendin‐4. Key Results Exendin‐4 modestly improved dyslipidaemia, but markedly decreased atherosclerotic lesion severity and area (−33%), accompanied by a reduction in monocyte adhesion to the vessel wall (−42%) and macrophage content in the plaque (−44%). Furthermore, exendin‐4 reduced hepatic lipid content and inflammation as well as hepatic CD68+ (−18%) and F4/80+ (−25%) macrophage content. This was accompanied by less monocyte recruitment from the circulation as the Mac‐1+ macrophage content was decreased (−36%). Finally, exendin‐4 reduced hepatic chemokine expression in vivo and suppressed oxidized low‐density lipoprotein accumulation in peritoneal macrophages in vitro, effects dependent on the GLP‐1 receptor. Conclusions and Implications Exendin‐4 reduces inflammation in both the liver and vessel wall by reducing macrophage recruitment and activation. These data suggest that exendin‐4 could be a valuable strategy to treat NASH and atherosclerosis simultaneously.